Behavioural responses of stable flies to cattle manure slurry associated odourants. Issue 1 (2nd January 2015) - TANGTRAKULWANICH, K.; ALBUQUERQUE, T. A.; BREWER, G. J.; BAXENDALE, F. P.; ZUREK, L.; MILLER, D. N.; TAYLOR, D. B.; FRIESEN, K. A.; ZHU, J. J.
Abstract Stable flies (Stomoxys calcitrans [Diptera: Muscidae] L.) are blood‐feeding synanthropic pests, which cause significant economic losses in livestock. Stable fly antennae contain olfactory sensilla responsive to host and host environment‐associated odours. Field observation indicated that the abundance of stable flies increased significantly in grasslands or crop fields when cattle manure slurry was applied. Major volatile compounds emanating from manure slurry were collected and identified. Behavioural responses of stable flies to those compounds were investigated in laboratory bioassays and field‐trapping studies. Results from olfactometer assays revealed that phenol, p‐cresol and m‐cresol were attractive to adult stable flies. When tested individually, attraction was higher with lower dosages. Stable flies were most attracted to blends of phenol and m‐cresol or p‐cresol. Traps with binary blend lures caught more stable flies in field trials as well.